ProteÃnas de sementes de Amburama Cearensis (Allemao) A. C. Smith: Valor Nutricional e bioatividade contra patÃgenos e vetores de doenÃas - Davi Felipe Farias (2009)
Amburana cearensis (Allemao) A. C. Smith, usually known in portuguese language as âImburana-de-Cheiroâ or âCumaruâ, is a leguminous tree, subfamily Papilionoideae with common occurrence in âCaatingaâ Dominium. Despite the numerous ethnobotanical uses, few studies report biological activities of medical interest and / or agribusiness for this species or yet its utilization as food for humans and / or animals. This study aimed to evaluate the proteins of A. cearensis on its nutritional value associated with its biochemical characterization and as to the presence of bioactivity against bacteria, yeasts and filamentous fungi, all pathogens of humans, animals or plants of economic importance, and also against the vectors of disease, Aedes aegypti and Ae. albopictus. For this, seeds were collected in areas of caatinga trees in the municipality of QuixadÃ - CE and, subsequently, dried and finely ground. The seeds of A. cearensis have high nutritional potential, evidenced by the high content of proteins (22.69  0.81 g 100 g-1), lipid (24.45 2.02 g 100 g-1) and dietary fiber (34.75 1.78 g 100 g-1), keeping smaller quantities of starch (11.43 0.18 g 100 g-1), of total sugars (5.60 0.09 g 100 g-1) and minerals (4.51 0.21 g 100 g-1). Its amino acid composition is comparable to that of soybeans and beans. Moreover, the seeds have moderate levels of antinutritional factors, being detected only trypsin inhibitory activity (27.41 Â 0.03 gTI Kg-1), urease activity (434 Â 34 U kg-1) and some secondary metabolites such as tannins, phenols, flavones, flavonols, and xantone steroids. Chemical components, probably of low molecular mass present in seeds flour incorporated into diets, seem to interfere with their acceptance and use by animals since when the protein fraction (F0/90), obtained from its soluble protein, was incorporated into the balanced diet, the rats accepted well the diets and their performance indicated that F0/90 a good source of protein, comparable to major sources of vegetable protein such as soy and beans. Proteins of A. cearensis seeds are mainly composed of globulins (74.43 g 100 g-1) and albumins (14.23 g 100 g-1), with smaller quantities of glutelin basic proteins (10.07 g 100g-1), prolamins (1.20 g 100 g-1) and glutelin acidic proteins (0.07 g 100 g-1). The seeds crude extract (GE) offers a wide variety of proteins as shown by electrophoretic profiles with a predominance of proteins with apparent molecular mass over 45.0 kDa. The seeds of A. cearensis show also high bioactive potential, especially the activities of their majority proteins (albumins and globulins) against the growth of human pathogenic bacteria and yeast and phytopathogenic filamentous fungi, and against larvae of Aedes aegypti and Ae. albopictus. The inhibitory activity of the growth of phytopathogenic fungi concentrated in the albumins F70/90 fraction, being rich in proteins of low molecular mass (<30 kDa). Thus we can conclude that F0/90 is a good source of protein food when compared to other plant sources already used by the population. In addition, the globulins and albumins of A. cearensis are promising sources of bioactive proteins to be studied further and in greater purity.